High methoxyl pectin from the soluble dietary fiber of passion fruit peel forms weak gel without the requirement of sugar addition. (15th October 2020) - Abboud, Kahlile Youssef; Iacomini, Marcello; Simas, Fernanda Fogagnoli; Cordeiro, Lucimara M.C.
Highlights: Rheological properties and flow behaviours of passion fruit peel pectins (PFPP) were evaluated. PFPP (1–4 %, w/w) in water dispersions or in the presence of sucrose at 25 % and 50 % (w/w) at pH 3 were prepared. Shear-thinning non-Newtonian behaviour was observed for PFPP in water dispersions or in the presence of sucrose. Dynamic oscillatory tests showed a gel-like behaviour, even without sucrose addition. PFPP has divergent behaviour from commercial HMP, since it does not require sucrose or low pH to form gel. Abstract: Passion fruit peel (PFP) is a by-product from the fruit processing industry, accounting for approximately 50 % of the fruit weight. It is well known for its health properties, although few studies evaluated its rheological properties. PFP polysaccharides (PFPP) contain a high methoxyl pectin (HMP), specifically a 70 % methyl-esterified homogalacturonan. Flow behaviour analysis of PFPP (with or without sucrose) revealed a shear-thinning non-Newtonian behaviour. Dynamic oscillatory tests showed a weak gel-like behaviour, even without sucrose addition. Moreover, under simulated pasteurization process PFPP maintained its gel structure. Taken together we demonstrated that PFPP has divergent behaviour from commercial HMP, since it does not require sucrose or low pH to form gel. The present work reinforces the use of PFP as a source of soluble dietary fibres and pectins, providing its alternative application as a rheological modifier in a wide range of products, including those with low sugar.